A clinicopathological study and prognostic factor analysis of 177 salivary duct carcinoma patients from The Netherlands. Issue 4 (23rd March 2018) - Boon, Eline; Bel, Miranda; van Boxtel, Wim; van der Graaf, Winette T. A.; van Es, Robert J. J.; Eerenstein, Simone E. J.; Baatenburg de Jong, Robert J.; van den Brekel, Michiel W. M.; van der Velden, Lilly‐Ann; Witjes, Max J. H.; Hoeben, Ann; Willems, Stefan M.; et al.
Abstract : Salivary duct carcinoma (SDC) is a subtype of salivary gland cancer with a dismal prognosis and a need for better prognostication and novel treatments. The aim of this national cohort study was to investigate clinical outcome, prognostic factors, androgen receptor (AR) and human epidermal growth factor receptor 2 (HER2) expression. SDC patients diagnosed between 1990 and 2014 were identified by the Nationwide Network and Registry of Histo‐ and Cytopathology in the Netherlands (PALGA). Subsequently, medical records were evaluated and pathological diagnoses reviewed. Data were analyzed for overall survival (OS), disease‐free survival (DFS), distant metastasis‐free survival (DMFS) and prognostic factors. AR was evaluated by immunohistochemistry (IHC), HER2 by IHC and fluorescent in‐situ hybridization. A total of 177 patients were included. The median age was 65 years, 75% were male. At diagnosis, 68% presented with lymph node metastases and 6% with distant metastases. Median OS, DFS and DMFS were 51, 23 and 26 months, respectively. In patients presenting without distant metastases, the absolute number of positive lymph nodes was associated with poor OS and DMFS in a multivariable analysis. AR and HER2 were positive in 161/168 (96%) and 44/153 (29%) tumors, respectively, and were not prognostic factors. SDC has a dismal prognosis with primary lymph node involvement in the majority of patients. The absolute number of lymph node metastases was found to be the only prognostic factor for DMFS and OS. AR expression and—to a lesser extent—HER2 expression hold promise for systemic treatment in the metastatic and eventually adjuvant setting. Abstract : What's new? Salivary duct carcinoma (SDC) is a rare and often fatal malignancy. Little is known about associations between its pathological features and clinical outcome. In this study, clinicopathological factors were analyzed for 177 patients diagnosed with SDC in The Netherlands between 1990 and 2014. The data show that median overall survival (OS) and distant metastasis‐free survival (DMFS) were 51 and 26 months, respectively. At diagnosis, 68% of patients presented with lymph node metastases. Lymph node positivity was associated with poor OS and poor DMFS. The absolute number of metastatic lymph nodes was the only significant prognostic factor for survival in a multivariate analysis. Androgen receptor and human epidermal growth factor 2 (HER2) were positive in 96% and 29%, respectively and were not a prognostic factor.